Drainage levels on bean in lowland - Rosa, Jadir Aparecido (Pesquisa Agropecuaria Brasileira, 1993)
The effect of different drainage levels on bean (Phaseolus vulgaris L.) productions in 1988/89 and 1989/90 harvest seasons, in a drained lowland gley humic soil in Ponta Grossa, Paraná, Brazil, was studied with the objective of utilizing alternative crops to rice in these areas. Three parallel drains were built, 25 m apart from each other. The levels of drainage were obtained by keeping the central drain full a water. The water table heights were measured in observation wells installed perpendicularly to the drains and 2 m apart from each other. The work was conducted in four repetitions, and in each harvest season four varieties were studied. The bean yielded better in the less drained treatment in the harvest season of 88/89 and in the more drained treatment in the 89/90 harvest season, due to variation of the climate between the years.